Fenomena Doom Spending: Perilaku Gen Z dalam Menabung - Muhammad Habib Zaki; Muhamad Jikran; Ridwan Kusnaedi; Sri Mulyeni (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
This phenomenon of anxiety-driven spending refers to excessive purchasing behavior that occurs as a response to economic uncertainty and pessimistic views about the future. It is commonly found among Generation Z, who have grown up in the digital era with easy access to various shopping platforms and digital financial services. This study aims to investigate the factors that make Generation Z more likely to experience difficulties in saving money and to examine the impact of this spending behavior on their financial condition. The data were analyzed using content analysis techniques to identify the relationships among variables that influence the financial behavior of Generation Z.The findings indicate that excessive spending is influenced by several key factors, including psychological conditions such as stress and anxiety, the influence of social media, low levels of financial literacy, poor self-control, easy access to digital financial services such as pay-later features, and behavioral biases such as overconfidence. These factors encourage Generation Z to prioritize instant gratification over long-term financial planning. As a result, their saving habits tend to decline, which may lead to financial difficulties in the future. Therefore, improving financial literacy, strengthening self-control, and promoting the wise use of financial technology are essential to reducing excessive spending behavior and increasing saving awareness among Generation Z.